What are Farmer Household Coping Strategies for Facing Crop Loss: Evidence from Indonesia - Feryanto; Harianto; Rosiana, Nia (The Indonesian Forestry Certification Cooperation, 2023)
The climate change that has occurred in the last decade has seriously impacted food availability and price pressures from the macro side, as well as the sustainability of farming activities and the welfare of farmers from the micro side. One form of climate change is crop failure; thus, to anticipate crop failure, farming households implement coping strategies to survive well. This study aimed to analyse the coping strategies used by farm households to deal with crop failures. The data used in this study were sourced from the Indonesian Family Life Survey (IFLS) conducted in 2007 and 2014. There were 3338 samples of farming households in a panel data format that could be used in the analysis. The analytical method used in this study uses a fixed effects approach at the household and rural levels to avoid potential bias from endogeneity and heterogeneity problems. The results showed that the coping strategies adopted by farming households were more likely to sell livestock and household assets and increase the number and frequency of loans. Reducing consumption has not been statistically proven as a coping strategy chosen by farming households facing crop failure.